The Role and Thought of The Nahdlatul Ulama-Muhammadiyah On Humanity - Suprapto; Lidiawati; Mahatva Yoga Adi Pradana; Ali Maksum (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Concern for humanitarian and health issues, several parties including NU and Muhammadiyah were involved inhandling the pandemic. Organizing the community in several aspects, such as appeals in mosques, appeals toeducational institutions and Islamic boarding schools, appeals for health protocols, and appeals forvaccinations. Muhammadiyah instructs that educational activities at all levels are aligned with government policieswhich are coordinated through the relevant assemblies. Through NU Care-Laziznu, they carried out a movementto help the poor or residents affected by the COVID-19 pandemic. NU formed a covid task force to mobilizeNU residents to help residents affected by COVID-19. NU as a student movement organization, is activelyinvolved in the struggle of the Indonesian nation. Islam Nusantara and Islam Berkejuan are the first,emphasizing locality with Islam, while the second focuses on globalization. Through the movement in Islamicboarding schools, NU as a space for religious studies (educational function), dialogue with local culture (sociocultural function) and training on problems in society (socio-political function). Tajdid initiated byMuhammadiyah is to put a solid religious view in the building of faith based on the Al-Quran and As-Sunnahand develop it for a progressive and civilized life. In its acceptance of ijtihad, the tarjih assembly is based on threemain points, namely: 1) ijtihad bayani (explaining the mujmal texts of the Qur'an and Hadith); 2) ijtihad qiyasi(stipulating legal provisions that do not exist in the Al-Quran and Hadith; 3) ijtihad istishlahi (stipulating lawsthat do not have texts specifically based on illat). Keywords: NU, Muhammadiyah, Humanity, Tajdid, Ijtihad